SEA SAND MINING ZONATION THROUGH THE INTEGRATION OF OCEAN DYNAMIC AND GIS IN RIAU ISLAND WATERS - Asmi M.Napitu; Dudung M.Hakim; Nining S.Ningsih; - Albert D. (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2007)
Sea-sand mining has both advantages particularly in its destructive capabilities. The damages caused by sea-sand mining are mostly due to the unorganized mining zones. In order to minimize the negative effects of mining activities, the well-organized mining zones that have evaluated all related aspects are required. There are several aspects which are closely related to the sea-sand mining zones , one of those is hydro-oceanography aspects in its relation with the sea environments. A comprehensive analysis can be made by integrating hydrooceanography and GIS as a system of both data-organizer and software. This method is supported by using the remote sensing technology as a verification data comparison to the results of hydrooceanography analyses. The application of image analysis as a verification tool is a good method to proof the results given by the numerical simulation model. In this study, we use the Landsat images as the data analysis have indicated that the mining can be continously conducted in several locations without imposing any hazardous impacts to the adjacent environment. By considering the results above, in integrated system between the numerical model and the GIS in highly effective as a foundation to determine the mining zone where the negative effects of the oceanographic-dynamical-changes on the environment due to the mining activities can be easily recognized and predicted. Keyword: Geographic Information System, Hydro-oceanography, Image Analysis.